Seleção de estratégias de crescimento e entrada em novos negócios em empresas de tecnologia da informação - Rabêlo Júnior, José Marcos Saraiva (2010)
Strategies such as downsizing, reorganization, restructuring, and cost reduction can be used by an enterprise as a way of improve its performance. But there is a limit to which the programs efficiency can increase profits, making the emphasis on the search for growth is an increasingly common perception. In this scenario, tools that assist the entrepreneur to decide on what strategies and methods are most appropriate growth have a high degree of importance. This study aimed to assess the adequacy of model Garcez (2005), focused on selecting strategies for growth and entry in new businesses, companies belonging to the productive arrangement of Fortress of information technology, with the participation of 20 companies. After the survey and analysis of episodes of growth occurring in these businesses, we performed the same framework of the matrix suggested by the author, noting that the model does not present fully adequate when applied to an economic activity formed predominantly micro and small enterprises. Was added to research an case study conducted in TOTVS, the largest software the country, having been found a better match between the methods proposed by the author and successful episodes experienced by organization. As a contribution, this research was to verify the appropriateness of the placement of some methods in matrix Garcez (2005) and the suggestion of appropriateness of placement methods, which do not showed positive results in new quarters. As an practice contribution, showed a tool to aid decision making in choice of strategies and methods of growth and entry into new businesses that have a higher probability of success with less risk.